2019
DOI: 10.1038/s41593-019-0470-8
|View full text |Cite
|
Sign up to set email alerts
|

Learning task-state representations

Abstract: Arguably, the most difficult part of learning is deciding what to learn about. Should I associate the positive outcome of safely completing a street-crossing with the situation "the car approaching the crosswalk was red" or "the approaching car was slowing down"? In this Perspective, we summarize our recent research into the computational and neural underpinnings of "representation learning"-how humans (and other animals) construct task representations that allow efficient learning and decision making. We firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
290
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(304 citation statements)
references
References 95 publications
14
290
0
Order By: Relevance
“…Context may also hold structural information that can be generalised across events (e.g., many behaviours which are acceptable at home are not acceptable when visiting others) (Gershman, 2017). There is evidence that such structural knowledge is encoded in the medial temporal lobe and ventral PFC (Behrens et al, 2018;Niv, 2019). Our results complement this work by identifying representations in FPl that may support a mapping between private states and public actions that are appropriate for the current context.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Context may also hold structural information that can be generalised across events (e.g., many behaviours which are acceptable at home are not acceptable when visiting others) (Gershman, 2017). There is evidence that such structural knowledge is encoded in the medial temporal lobe and ventral PFC (Behrens et al, 2018;Niv, 2019). Our results complement this work by identifying representations in FPl that may support a mapping between private states and public actions that are appropriate for the current context.…”
Section: Discussionsupporting
confidence: 64%
“…Recent years has seen an interest in how the brain encodes structured representations of the world for efficient learning and decision-making (Behrens et al, 2018;Niv, 2019;Radulescu, Niv, & Ballard, 2019). In these scenarios, context may be particularly important for adaptive behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…The precise computations that mediate model-contingent credit assignment depend on the brain's internal representation of the task state-space [2][3][4]32,33 . In many laboratory tasks, including ours, more than one task representation is possible 2,33 .…”
Section: Ofc Representation Of Task Space Respects Relational Structurementioning
confidence: 99%
“…The precise computations that mediate model-contingent credit assignment depend on the brain's internal representation of the task state-space [2][3][4]32,33 . In many laboratory tasks, including ours, more than one task representation is possible 2,33 . However, to benefit from the relational knowledge, any such representation must differentiate the related stimuli (A,B) from the control stimulus (C) so that AB outcomes can cause learning on both A and B but not C. For example, one possible representation is to maintain a single variable encoding the state of the AB pair 2 and a second variable encoding the state of C.…”
Section: Ofc Representation Of Task Space Respects Relational Structurementioning
confidence: 99%
“…In rodents, increased neural synchrony between the hippocampus and mPFC has been observed at decision points in which memory must be used to guide future behavior (Benchenane et al, 2010;Jones & Wilson, 2005). In humans, functional magnetic resonance imaging (fMRI) studies have demonstrated that the orbitofrontal cortex (a region in the ventral medial prefrontal cortex) represents goal state representations that are not explicitly instructed but rather inferred on the basis of past experience (Niv, 2019;Schuck, Cai, Wilson, & Niv, 2016;Schuck et al, 2015). Moreover, the hippocampus and ventromedial PFC (vmPFC) show functional coupling as individuals learn which features of an object are relevant for determining its category, and thus should be attended (Mack et al, 2016).…”
Section: Introductionmentioning
confidence: 99%